Active inflammation and structural change in early active axial spondyloarthritis as detected by whole-body MRI. Issue 6 (26th June 2012) - Althoff, Christian E; Sieper, Joachim; Song, In-Ho; Haibel, Hildrun; Weiß, Anja; Diekhoff, Torsten; Rudwaleit, Martin; Freundlich, Bruce; Hamm, Bernd; Hermann, Kay-Geert A
Abstract : Objective: To evaluate active inflammatory lesions (AIL) and structural changes (SC) in patients with active non-radiographic axial spondyloarthritis (nr-axSpA) compared with patients with ankylosing spondylitis (AS) on whole-body MRI (wb-MRI). Method: 75 patients with active disease and a symptom duration of <5 years (39 with AS and 36 with nr-axSpA) were investigated with a comprehensive wb-MRI protocol and scored for AIL and SC in the spine, sacroiliac joints (SIJs) and non-axial manifestations. Results: 92% of patients with AS showed active inflammation in the SIJ, 53% in the spine and 94% and 39%, respectively, in the nr-axSpA group. There was a non-significant trend towards more inflammation in patients with AS compared with patients with nr-axSpA in SIJs and spine. Peripheral enthesitis/osteitis was more common in patients with AS (n=22) than in those with nr-axSpA (n=12) (p=0.05). SC were more common in patients with AS than in those with nr-axSpA, with significantly higher scores for SIJ fatty bone marrow deposition (FMD) in patients with AS (4.8±3.2) compared with those with nr-axSpA (2.4±2.7; p=0.001) and more frequent bone proliferation in the spine and the SIJ (p=0.02 and p=0.005, respectively). SIJ erosions were more common in AS (score 4.2±2.3) than in nr-axSpA (score 3.8±1.8) patients (not significant). Conclusions: Wb-MRI detects active inflammation and SC more frequently in the SIJs than in the spine. Half of the patients showed inflammation in non-axial sites. Active inflammatory and structural lesions were present both in patients with AS and those with nr-axSpA, being only slightly more common in patients with AS.